THE BINĀ' AL-MAQĀLAH OF JAMĀL AL-DĪN AHMAD IBN TĀWŪS AND ITS PLACE WITHIN THE MATHĀLIB GENRE - Afsaruddin, Asma (Journal of Semitic studies, 1996)
ASMA AFSARUDDIN; THE BINĀ' AL-MAQĀLAH OF JAMĀL AL-DĪN AHMAD IBN TĀWŪS AND ITS PLACE WITHIN THE MATHĀLIB GENRE, Journal of Semitic Studies, Volume XLI, Issue 1,